Genetics of Fukuyama Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The Fukuyama congenital muscular dystrophy (FCMD) chromosome analysis has been further defined at the University of Tokyo; Department of Pediatrics, Tokyo Women's Medical College; Kobe General Hospital; Aichi Welfare Center, Kasugai; and Nagoya City University Medical School, Japan.